Energy efficiency-based downlink resource allocation in cognitive small cell networks - Ya-nan JIA; Dian-wu YUE (Tongxin xuebao)
Joint downlink spectrum resource block(SRB) and power allocation was studied based on OFDMA n cog-nitive small cell networks.In a distributed framework, small cell base stations (SCBS) could share free spectrum re-sources with open access to maximize their energy efficiency (EE) respectively. The competition among SCBS made the dynamic resources allocation problem be modeled as a non-cooperative game. It was non-convex optimal to op-timize the EE in a fractional form under multiple interference constraints. The maximization problem was transmitted into an equivalent problem in subtractive form which could be solved from the sequential and parallel iteration points of view. After obtaining the SRB allocation strategies, the master game could be re-modeled as equivalent sub-games for solving the transmission power more easily. Simulation results show the proposed algorithm can converge to a Nash equilibrium and effectively improve system resources utilization and EE in interference-limited communication environments.